A quantitative geomorphic approach to predicting productivity of pink and chum salmon streams in southeast Alaska - Swanston, Douglas N.; McNutt, James A , joint author.; Meehan, William R. , joint author.; United States. Forest Service.; Pacific Northwest Forest and Range Experiment Station (Portland, Or.) (Portland, Or. : Dept. of Agriculture, Forest Service, Pacific Northwest Forest and Range Experiment Station, 1977)
Bibliography: p. 13-14. Mode of access: Internet. 2